ANALYSIS OF HYBRID HEATING SYSTEMS OF RESIDENTIAL BUILDINGS USING RENEWABLE ENERGY SOURCES - Uzakov , G.N.; Davlonov, Kh.; Toshmamatov, Bobir (Muqobil energetika, 2023)
The article presents schemes of hybrid heat supply systems based on traditional and renewable energy sources. A brief analysis of the existing hybrid heat supply systems was conducted and an improved hybrid heat supply system for a country house was proposed for the conditions of the south of the republic.